2020
DOI: 10.3390/cells9040984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of RNP Networks of PUM1 and PUM2 Post-Transcriptional Regulators in TCam-2 Cells, a Human Male Germ Cell Model

Abstract: Mammalian Pumilio (PUM) proteins are sequence-specific, RNA-binding proteins (RBPs) with wide-ranging roles. They are involved in germ cell development, which has functional implications in development and fertility. Although human PUM1 and PUM2 are closely related to each other and recognize the same RNA binding motif, there is some evidence for functional diversity. To address that problem, first we used RIP-Seq and RNA-Seq approaches, and identified mRNA pools regulated by PUM1 and PUM2 proteins in the TCam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…In total, 346 PUM1-regulated and 141 PUM2-regulated targets were identified in that study. About 90% of PUM-regulated targets were different for PUM1 and PUM2, and nearly 100% of all identified targets contained PBEs, thus validating the results [ 34 ]. Several other studies aimed at the global identification of human PUM1 and PUM2-regulated targets were performed in other human cell lines and using some methodological modifications compared to the study in TCam-2 cells.…”
Section: Expression Of Pumilio Proteins (Pum1/2) and Mrna Target Isupporting
confidence: 67%
See 2 more Smart Citations
“…In total, 346 PUM1-regulated and 141 PUM2-regulated targets were identified in that study. About 90% of PUM-regulated targets were different for PUM1 and PUM2, and nearly 100% of all identified targets contained PBEs, thus validating the results [ 34 ]. Several other studies aimed at the global identification of human PUM1 and PUM2-regulated targets were performed in other human cell lines and using some methodological modifications compared to the study in TCam-2 cells.…”
Section: Expression Of Pumilio Proteins (Pum1/2) and Mrna Target Isupporting
confidence: 67%
“…A global immunoprecipitation (IP) and mass spectrometry (MS)-based identification of PUM1- and PUM2-binding proteins showed that PUM1 and PUM2 indeed interact mainly with different groups of proteins, a majority of them representing RBPs. Combinatorial analysis of RNA immunoprecipitation (RIP) and RNA-Seq MS, as well as motif enrichment analysis for RNA-binding proteins in PUM1 and PUM2 mRNA targets, revealed that PUM1 and PUM2 form separate ribonucleoprotein networks [ 34 ], which resemble so-called “regulons” or “posttranscriptional operons”, as previously suggested for RBPs that recognize specific motifs in RNAs [ 41 ]. According to those networks, PUM1 and PUM2 may cooperate with varied protein cofactors to regulate mRNA target sub-pools responsible for unique pathways.…”
Section: Expression Of Pumilio Proteins (Pum1/2) and Mrna Target Imentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include NANOS2 in this study because it is not expressed at that early stage of germline development represented by the TCam-2 cells [ 16 ]. Our transcriptome analysis of this cell line by RNA-sequencing (RNA-Seq) showed that both NANOS1 and NANOS3 are expressed at low levels at that stage (1.7 and 2.1 FPKM, respectively) [ 29 ]. Therefore, we overexpressed NANOS1 and NANOS3, followed by RNA sequencing (RNA-Seq) and differential gene expression (DGE) analysis to identify mRNAs potentially downregulated by these post-transcriptional repressors.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously identified FOXM1 mRNA as a direct target of PUM1 [ 29 ]. Thus, we asked whether NANOS3 and PUM1 cooperate in FOXM1 mRNA repression.…”
Section: Resultsmentioning
confidence: 99%